Taste dysfunction following radiotherapy to the head and neck: A systematic review. (April 2021) - Gunn, Lucinda; Gilbert, James; Nenclares, Pablo; Soliman, Heba; Newbold, Kate; Bhide, Shree; Wong, Kee Howe; Harrington, Kevin; Nutting, Chris
Highlights: Taste dysfunction is common, affecting 70–90% of people during radiotherapy with bitter and salt taste qualities affected most severely. Taste dysfunction typically recovers partially post-radiotherapy but usually there is lingering dysfunction months to years after radiotherapy. Minimising radiotherapy dose to the oral cavity and, specifically, the anterior two-thirds of the tongue is likely to reduce the risk of taste dysfunction. Proton beam therapy and bite blocks may help to achieve this risk reduction. Taste dysfunction is associated with a number of clinically important sequelae, including weight loss, xerostomia and reduced quality of life. Abstract: Background: An intact sense of taste provides pleasure, supports sustenance and alerts the body to toxins. Head and neck cancer (HNC) patients who receive radiotherapy (RT) are high-risk for developing radiation-induced taste dysfunction. Advances in RT offer opportunities for taste-preserving strategies by reducing dose to the gustatory organs-at-risk. Methods: PubMed, Medline and EMBASE were searched for publications reporting on taste, RT and HNC. Randomised trials, cohort studies and cross-sectional studies were included. Results: 31 studies were included in this review. Meta-analysed prevalence of acute taste dysfunction following RT was approximately 96% (95% CI 64 to 100%) by objective measures and 79% (95% CI 65 to 88%) by subjective measures, with the majority of patients showing at least partial recovery. Long-term dysfunction was seen in 25% of patients. Taste dysfunction was associated with sequalae including weight loss and reduced quality-of-life (QoL). Taste dysfunction was more common when the oral cavity, and specifically the anterior two-thirds of the tongue, was irradiated, suggesting a dose constraint for taste preservation might be feasible. Proton beam therapy and customised bite blocks reduced dose to the gustatory field and subsequent loss of taste. Conclusions: Taste dysfunction following RT is common and negatively affects patients' nutritional status and QoL. Decisions about treatment strategies, including choice of RT modality, dose distribution across the gustatory field and the use of adjuncts like bite blocks may be beneficial. However, evidence is limited. There is a pressing need for randomised studies or large prospective cohort studies with sufficient adjustment for confounders.